Skomager, bliv ved din læst! Om politologiske leksika, politik i leksika og leksikografiske værktøjer - Pálfi, Loránd-Levente; Leroyer, Patrick; Wagner, Adam; Vesterdal, Spiros Divaris (LexicoNordica, 2008)
Seeing dictionaries as the lexicographic tools they truly are, this paper seeks to give a critical overview of Danish dictionaries of political science published at the turn of the 21st century. The methodology applied in our research is new and is based on the calibration principle of dictionaries as lexicographically structured reference sources. The focus of the study is on external access structures, the article stock, and the treatment of data from the user’s perspective. Ideally, LSP dictionaries should have advanced needs-adapted access structures, devised according to clearly defined, functional principles. The dictionaries examined in this paper, however, leave much to be desired in this respect. Therefore, in several cases functional changes and improvements are proposed. Also the problems of biased definitions and their questionable value to the user are discussed. Furthermore, it is suggested that the optimal LSP dictionary should include not only encyclopaedic but also linguistic information, as a combination of communicative and cognitive functions enhances external accessibility of any lexicographical product.